Capability of Three Yeast Species in Suppressing Green Mold (Penicillium digitatum) on Siam Citrus Fruit (Citrus nobilis) - Hartati, Sri; Utari, Elinda Dwi; Rasiska, Siska; Istifadah, Noor (CROPSAVER, 2022)
Green mold is one of the main diseases in citrus fruits caused by Penicillium digitatum. One of the managements that can be used to control this disease is by using yeasts as antagonistic agents. The objective of this study was to evaluate the ability of yeast to suppress Green mold caused by P. digitatum in siam citrus (Citrus nobilis Lour.). The study was conducted using a completely randomized design. The treatments were the application of yeast, consisting of Aureobasidium pullulans isolate Dmg 11 DEP, Rhodotorula minuta isolate Dmg 16 BE, Candida tropicalis isolate Lm 13 BE, fungicide benomyl, and control. The results showed that A. pullulans isolate Dmg 11 DEP, C. tropicalis isolate Lm 13 BE, and R. minuta isolate Dmg 16 BE were able to suppress the growth of P. digitatum in vitro on dual culture method, with suppression levels ranged from 14.64%-21.02%. The greatest suppression was caused by R. minuta isolate Dmg 16 BE. The formation of volatile compounds test results were ranged from 14.51%-34%, and the highest suppression was on C. tropicalis isolate Lm 13 BE. Application of the yeasts on siam citrus fruit was able to reduce the pathogen’s growth, and the suppressions were 28.87% to 68.72%. R. minuta isolate Dmg 16 BE caused the highest suppression.